LANDSCAPE AND LANDSCAPES IN THE POETRY OF CZESŁAW MIŁOSZ, FRIEDRICH HÖLDERLIN AND JOHANNESA BOBROWSKI - Fieguth, Rolf (Porównania, 2017)
The author discusses a number of landscape poems, written by C. Miłosz in different periods of his life, and compares them with selected works of the Suabian F. Hölderlin and of the Tilsit poet J. Bobrowski. Each of them returns frequently to the landscape of his childhood, lost not only by the wars (Miłosz and Bobrowski), but also by existential alienation (Hölderlin). Each of them sees in it a symbol of the heavenly homeland. All three are in an opposition to the conventional versification systems of their times and their national literatures, but Miłosz and Bobrowski are moreover linked by their common longing for their native Neman regions. Miłosz’s war time poetry on the Mazovian plains shows some striking parallels with Bobrowski’s „Sarmatian” poetry stemming from his experiences of the same period. Miłosz’s treatment of European and notably American landscapes leads to a creation of mixed, American-Lithuanian or giant panoramic landscapes bearing distinctly mythic and metaphysical accents, which can be found, in a different set up, also in the other poets. These parallels and ‘common situations’ are not due to some explicit dialogue between them, but to a common Biblical, antique and postmedieval tradition, and also to a highly difficult, but nevertheless geographically close neighbourhood.